The Future of Bricks and Mortar - A Financial Approach to investigating how technology will change the demand for real estate. - Lim, Pau Ling Alvin (2008)
Technology has changed the way we live and work. It also change the way companies create markets, deliver products and serve customers. The internet is said to threaten the role of real estate, which is to provide spaces for people and for business to conduct their business. Proponents for real estate say that people and businesses will always need real estate while its distracters are calling for its demise. Some are predicting a merger of bricks and internet, also known as “Clicks and Mortar". Who is right then? This dissertation seeks to find out how technology will impact the demand for real estate using a quantifiable financial approach.